Cronkhite-Canada Syndrome: Review of the Literature. (28th November 2013) - Kopáčová, Marcela; Urban, Ondřej; Cyrany, Jiří; Laco, Jan; Bureš, Jan; Rejchrt, Stanislav; Bártová, Jolana; Tachecí, Ilja
Abstract : Cronkhite-Canada syndrome is a rare disease characterised by diffuse polyposis of the gastrointestinal tract, diarrhoea, weight loss, abdominal pain, cutaneous hyperpigmentation, dystrophic changes of fingernails, and alopecia. The etiology is probably autoimmune and diagnosis is based on history, physical examination, endoscopic findings of gastrointestinal polyposis, and histology. The disease is very rare; about 450 cases have been described in the literature so far. We present a review of the literature with our own picture documentation of this rare condition.